Filtros de arcilla y cascarilla de arroz, incidencia en remoción de carga orgánica en aguas residuales de la ciudad de Portoviejo - Zambrano Cedeño, Ives Santiago (2019)
The purpose of this work was to evaluate the incidence of filtering media of clay and rice husk with a gravel base and silica sand, in the removal of organic load from the effluent of the oxidation lagoon of the city of Portoviejo. The experiment was carried out under a completely randomized, unifactorial experimental design, where a total of six treatments were proposed with three repetitions each, generating 18 filters. A sample was taken for each filter once a week for three weeks, then they were taken to the laboratory where they were analyzed for BOD5, COD and pH. For the water in the reservoir tank, analysis of the same parameters was carried out to compare the results and determine the efficiency of the filters; where a value of 843 mg / dm3 of BOD5 was obtained. The results obtained were satisfactory since the A2B2 treatment of the second week which was packed with rice husk, reached a BOD5 of 424 mg / dm3, obtaining a reduction of 50.29%. These results did not reach below the permissible limit for discharges to sewer water, which would not allow the use of these filters as a pretreatment for wastewater, because the result obtained was not below 250 mg / dm3, stipulated by the Unified Text of Secondary Environmental Legislation (2014).